Mitochondrial DNA Mutations and Pediatric Neurological Disorders: A Systematic Review - Putu Rika Anjani; Erika Aini Putri S; dr. Iffa Maulida Wiedy Astari; dr. Yudi Wahyudi; Veriantara Satya Dhika (Medicinus, 2026)
Background: Mitochondrial DNA mutations are increasingly recognized as a significant cause of neurological disease in the pediatric population, yet the breadth of genotype–phenotype associations, diagnostic yield, and clinical spectrum across different study designs and populations have not been systematically synthesized. Methods: A systematic search of PubMed, EMBASE, and Scopus was conducted from inception until 10 May 2026 to identify studies evaluating mitochondrial DNA mutations in pediatric patients with neurological or neurodevelopmental disorders. All authors independently performed study selection; discrepancies were resolved through discussion. Data extraction and risk-of-bias assessment were performed using standardized tools adapted for observational study designs. Narrative synthesis was conducted. Result: Twenty-one studies met inclusion criteria, encompassing cohort, case-control, and diagnostic studies from twelve countries. Leigh syndrome and mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes were the most frequently reported phenotypes. Recurrent mutations in MT-ATP6, MT-TL1, MT-ND3, MT-ND5, and MT-ND6 were identified across studies. Autism spectrum disorder studies yielded mixed results regarding mitochondrial DNA involvement. Overall risk of bias ranged from low–moderate to high. Conclusions: Mitochondrial DNA mutations contribute to a wide spectrum of pediatric neurological disease, with Leigh syndrome and mitochondrial encephalomyopathy predominating. Standardized phenotyping and comprehensive sequencing approaches are needed for future multicenter studies.